Sistem Informasi Administrasi Kependudukan (SIASIK) Pada Kelurahan Berbasis Web - Mustika, Wida Prima; Kumalasari, Jefina Tri; Fitriani, Yuni; Abdurohim, Ahmad (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Sub-district in general acts as a community service center in certain areas. One of the sub-district services is to administer population administration letters. The main problem in sub-district in general there is no system that helps in storing Population Administration data. The Demography Administration Information System aims to carry out administration such as (Transfer Letter, Death Certificate, etc.). This system is also for handling a lot of documents so that the making of application letters can be faster and more efficient. In gathering information, the authors made direct observations and direct interviews with parties related to the administration of the village. making using the Demography Administration Information System with SDLC Waterfall method. In its development, planning is made starting from collecting all data and making designs to build system requirements. The programming language used is web-based. The advantages obtained in this application are made to make it easier for officers in handling a lot of documents, such as difficulty finding and printing data. And for the sake of data security to avoid data loss, data duplication and data manipulation. The system using the Sublime application with the programming language PHP, jquery, and Enterprise Architect 7.0. The result of this research is a village administration program that can assist the administrative activities of the village.